The influence of vaginal microbiota on the pregnancy outcome of artificial insemination with husband's sperm based on microscope images combined with PCR fluorescence method - Yanling Xing; Wei Wang; Na Wan; Dongmei Zhang; Mei Shan; Guan Wang (SLAS Technology)
The vaginal microbiota plays an important role in reproductive health, especially in the process of artificial insemination. The imbalance of microbiota may affect pregnancy outcomes. Therefore, this study aims to explore the composition of vaginal microbiota and its impact on artificial insemination pregnancy outcomes, combined with microscopic images and PCR fluorescence methods, in order to provide scientific basis for improving the pregnancy outcomes of husband sperm artificial insemination. This study included female patients who underwent artificial insemination with husband's sperm and collected reproductive tract samples. By observing the microbial community morphology in the sample under a microscope and analyzing microbial DNA using PCR fluorescence method, the microbial ecological status is evaluated. Among women with successful pregnancy, the proportion of beneficial bacteria (such as lactic acid bacteria) is higher, while the abundance of pathogenic bacteria is significantly reduced. Specific microbial markers detected by PCR fluorescence method are positively correlated with pregnancy rate. Therefore, the microecological state of the female reproductive tract has a significant impact on the pregnancy outcome of artificial insemination. Maintaining a good microecological balance, especially increasing the proportion of beneficial bacteria, can help improve the success rate of artificial insemination.